End-to-end QoS provisioning in mobile heterogeneous networks. - Xio Gao
The remarkable advances in information technologies bring a heterogeneous environment for mobile users and service providers. This heterogeneity exists in wireless access technologies, networks, user terminals, applications, service providers, and so on. The ability to provide seamless and adaptive quality of service in such a heterogeneous environment is key to the success of next-generation wireless communications systems. There has been a considerable amount of QoS research recently. However, the main part of this research has been in the context of individual architectural components, and much less progress has been made in addressing the issue of an overall QoS architecture for the mobile Internet. This article first summarizes the state-of-the-art QoS techniques and standardization activities, then examines in detail important challenges in building a ubiquitous QoS framework over the heterogeneous environment, and finally proposes a QoS framework integrating a three-plane network infrastructure and a unified terminal cross-layer adaptation platform to provide seamless support for future applications.
Keywords: Internet; Internet protocol; End-to-end QoS provisioning; Hierarchical policy management system; Information technologies; Mobile heterogeneous networks; Next-generation wireless communications systems